Managing uncertainty in healthcare interpreter-mediated interaction: On rendering question-answer sequences. (3rd April 2019) - Baraldi, Claudio; Gavioli, Laura
Abstract : This paper analyses healthcare interactions involving doctors, migrant patients and 'intercultural mediators' who provide interpreting services. Our study is based on a collection of 300 interactions involving two language pairs, Arabic–Italian and English–Italian. The analytical framework includes conversation analysis combined with insights from social systems theory. We look at question-answer sequences, where (1) the doctors ask questions about patients' problems or history, (2) the doctors' questions are responded to and (3) the doctor closes the sequence, moving on to another question. We analyse the ways in which mediators help doctors design questions for patients and patients understand and eventually respond to the doctors' design. While the doctor's question design aims at obtaining details which are relevant for the patients' care, it is argued that collecting such details involves complex interactional work. In particular, doctors need help in displaying their attention to their patients' problems and in guiding patients' responses into medically relevant directions. Likewise, patients need help in reacting appropriately. Mediators help manage communicative uncertainty both by showing the doctor's interest in what the patient says, and by exploring and rendering the patient's incomplete, extended and ambiguous answers to the doctor's questions.